The Effect of Urban Fortification on Public Space - (:unkn) unknown (My University, 2013)
This dissertation contributes to empirical studies on the spatial extent and intensity of urban fortification/security zones and their influence on urban public space. Urban public space has been based on creating open and safe environments for city dwellers. However, ultra-secure urban spaces have been found to filter citizens, restrict movement, and modify individual behavior. This first part of this study determines where security zones manifest themselves, quantify the fortification of the security zones, and measure the intensity of these spaces in three major U.S. cities. The second part of the study offers an explanation of how social and commercial activity is being affected by security zones.
Keywords: Urban Studies